Perceptions of me, conceptions of you: refining ideas of access to, and 'acceptance' within, the police organisational field. (24th March 2018) - Cram, Frederick
ABSTRACT: Ethnographers of the police have long drawn attention to the importance of gaining a degree of trust and acceptance from those they study. Reflexive accounts 'from the field' have emphasised the need to consider how one's own personal characteristics may shape the research relationship and impact on the validity of data collected. Little attention, however, has been paid to the implications for research access of the way in which police officers conceptualise their own role. In the study discussed here, significant attempts were made by some police officers to avoid being observed for the purpose of the research. One explanation for this is that the researcher's identity as a young, black male may have heightened the usual concerns about allowing outsiders to study frontline behaviour. The difficulty with this explanation is that different groups of police officers exhibited markedly different responses to the project, ranging from those who ducked and weaved their way out of participating, to those who enthusiastically 'created' opportunities for the researcher to observe police–citizen interactions. There is no evidence to suggest that those who were receptive to the research held less problematic views about race. Rather, it is argued that the more at ease police officers were with their particular policing role, the more open they were to being researched. This leads to the conclusion that reflexive accounts of the police–researcher relationship need to pay more attention to how police officers see themselves.